Comparative Toxicity, Phytochemistry, and Use of 53 Philippine Medicinal Plants - Clemen-Pascual, Lydia M (Archīum Ateneo, 2021)
The study compares the toxicity of 53 selected medicinal plants commonly used in the Philippines to treat various diseases. It uses as a benchmark Vitex negundo L., which was approved by the Philippine Food and Drug Administration as an herbal drug for cough and asthma after passing clinical trials for safety and efficacy. The methods were chosen for their simplicity and accessibility even for resource-limited laboratories. Extracts (95 % ethanol) of the medicinal parts of the plants were (1) chemically profiled using qualitative phytochemical tests that detect the presence of key classes of bioactive compounds; and (2) evaluated for toxicity using the brine shrimp (Artemia sp.) lethality assay (BSLA). General phytochemical screening revealed the presence of tannins in 50 plant extracts, alkaloids in 43, glycosides in 33, flavonoids in 31, steroids in 21, triterpenoids in 20, anthraquinones in 10, and saponins in 8. Extracts from eight plants had LC50 values lower than the potassium dichromate control (approximately 12 μg/mL) and were considered highly toxic; extracts from 21 plants had LC50 values between 12 μg/mL and 100 μg/mL and were considered moderately toxic; extracts from 19 plant extracts, including Vitex negundo and some common vegetables, had LC50 values between 100 μg/mL and 500 μg/mL, and were considered mildly toxic and likely to have reasonable safety margins; five plant extracts, including common vegetables, had LC50 values above 500 μg/mL and were considered essentially nontoxic. No apparent correlation could be found between toxicity and chemical diversity or a specific class of phytochemicals present. Our findings may serve as a guide for herbal drug and nutraceutical development, especially in prioritizing plants for more detailed safety studies.